Try Us with Riddles, Try Us with Structures: On the Element of Transformation in Structuralism as a Bridge from Modernity to Postmodernity - Hasan-Rokem, Galit (MiKAN, 2012)
The article discusses the important role of structuralism in the humanities and the social sciences of the twentieth century. Special emphasis is placed on some central figures in this school, primarily Claude Lévi-Strauss, and their shaping of structuralism’s conceptual framework, in particular their theoretical treatment of ’myth’. The article suggests, first, that we consider structuralism as an epistemological bridge from modernist to postmodernist modes of thought, and, second, that we view premodernity, modernity, and postmodernity not only as linear and chronological concepts but as analytical concepts in a synchronic paradigm. Significant to this perspective is the idea that transformation, rather than binary opposition, is the most important and seminal of Lévi-Strauss’ conceptual contributions. The study of folk literature, the article further reveals, was central to the development of structuralist thought and methodology. Special attention is paid to the contributions of structuralist methodologies to the study of riddles.